Population structure and distribution of Anadara tuberculosa Sowerby (1833) (Mollusca: Bivalvia) in the mangroves of Golfito and Playa Blanca, Puerto Jiménez, Golfo Dulce, Costa Rica. - Silva-Benavides, Ana Margarita (2015)
The density, population, length, yield and sex proportion of the Anadara tuberculosa Sowerby (1833) were studied in the mangroves of Golfito and Playa Blanca, Golfo Dulce, Costa Rica from 2008-2010. A. tuberculosa was more abundant in Golfito mangroves (2.77 units m2), than Playa Blanca mangrove (0.14 units m2). The average lengths were 42.1mm for Golfito (under the Costa Rican legal minimal length for exploitation: 47mm) and 48.35mm for Playa Blanca mangrove. Maximum densities in Golfito were measured in the outlet of Purruja River (mangrove of Purruja) and mangroves Congo, Ceibo y la Trocha. The average total weights were 24.48g for Golfito and 36.35g for Playa Blanca. The condition index (a meat yield measurement) was higher in Golfito (23.45%) than in Playa Blanca (17.01%). The male ratio was 1:1. These results suggest that A. tuberculosa population is declining in these mangroves. Therefore, it’s necessary to implement repopulation projects of the mollusc in the mangroves of Golfo Dulce, in conjunction with government authorities, NGOs and civil society. Mangrove workers and consumers are needed in that potential projects, to make the mollusc a sustainable natural resource exploited by different community members.